PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF METODE ARTIKULASI DAN TIME TOKEN SEBAGAI UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA KELAS X1 SMA N 1 TRIMURJO TAHUN PELAJARAN 2011/2012 - Rizki Hikmawati; Hening Widowati (UNIVERSITAS MUHAMMADIYAH METRO, 2013)
This research was the Classroom Action Research. The research was conducted caused the students lack in learning process actively. Therefore, the researcher applied Cooperative Learning Model Articulation Method and Time Token that considered the eagerness as the motivation for the students in order that they be able to follow the learning process actively. It is expected to have an impact of learning achievment obviously. This classroom action research has an objective to increase eagerness and students learning achievement of X1 class of Senior High School 1 of Trimurjo. From this research can be inferred that there were an increasing the eager to study of the students. It perceived to the activity of the students in pre-research towards the activity after doing research based on the increasing of evaluation product. The researcher recommend using Cooperative Learning Model Articulation Method And Time Token be able to apply in learning process in order to increase the eagerness and students learning achievement considered the time within the arranging of lesson plan.Kata kunci: artikulasi, time token, minat, hasil belajar